HEIGHT - LENGTH RELATION OF SHELLS IN THE INDIAN BACKWATER OYSTER CRASSOSTREA MADRASENSIS (PRESTON) OF THE COCHIN HARBOUR - NAIR, N UNNIKRISHNAN; NAIR, N BALAKRISHNAN (Fishery Technology, 2017)
Height-lent h relationship in Crassostrea madrasensis (Preston) showed an exponential trend and relation in the form, H=ALB. Deviations of actual values from the mean values consequent to the increase in size were noticed. eight and length approximated in oysters of less than 3.5 cm in height resulting in orbicular shape. In oyster of shell height 3.5 cm to 8 cm, increase in height is faster leading to an oval shape. Above 8 cm in height, the oysters become further elongated. Height-length relation is non-linear with an index (B value) of 1.1156. A linear relationship also holds good as the B value is not very much different from unity (H = Â 2.5424 + 2.0036L).